ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NET INTEREST MARGIN PADA BANK-BANK UMUM DI INDONESIA - PUSPITASARI, ELISA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: The purpose of this study is to analyzes the determinants of net interest margin of the public banking sector in Indonesian over period of 2009-2012. Independent variables are credit risk, operating cost, risk aversion, and transaction size. Research using purposive sampling method for taking samples. Analysis technique used is multiple linear regression analysis.The result of this research is credit risk has not effect to net interest margin. Furthermore, bank’s specific factor such as high operating costs contributes to high net interest margin.Transaction size has positive influence to net interest margin. Risk aversion has not effect to net interest margin. Keywords: net interest margin, credit risk, operating cost, risk aversion, transaction size.